2013
DOI: 10.1186/1471-2180-13-167
|View full text |Cite
|
Sign up to set email alerts
|

Ground Anthrax Bacillus Refined Isolation (GABRI) method for analyzing environmental samples with low levels of Bacillus anthracis contamination

Abstract: BackgroundIn this work are reported the results of a qualitative analytical method capable of detecting Bacillus anthracis spores when they are present in very low concentration in the soil. The Ground Anthrax Bacillus Refined Isolation (GABRI) method, assessed in our laboratory, was compared with the classic method. The comparison involved artificially anthrax-contaminated soil samples (500 spores/7.5 grams soil) and naturally contaminated soil samples collected in Bangladesh during a field investigation.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…The Ground Anthrax Bacillus Refined Isolation (GABRI) was performed as described by [ 36 ]. After incubation at 37°C for 24 hours the suspected colonies appearing whitish and without hemolysis were picked and spread on Columbia blood agar.…”
Section: Methodsmentioning
confidence: 99%
“…The Ground Anthrax Bacillus Refined Isolation (GABRI) was performed as described by [ 36 ]. After incubation at 37°C for 24 hours the suspected colonies appearing whitish and without hemolysis were picked and spread on Columbia blood agar.…”
Section: Methodsmentioning
confidence: 99%
“…Biopsy samples from skin lesions of each patient were directly cultured on 5% sheep blood agar at 37˚C overnight and a single colony was isolated as an independent strain. The colonies were identified using biochemical tests and PCR [18].…”
Section: Bacterial Strains and Dna Extractionmentioning
confidence: 99%
“…To detect B. anthracis from samples, the Ground Anthrax Bacillus Refined Isolation (GABRI) method was used (Fasanella et al, 2013a). The GABRI method is a sensitive method for isolation of B. anthracis spores from soil particles as it disrupts hydrophobic interactions between spores and the adhering solid matrices.…”
Section: Isolation Of B Anthracis From Soil Samples and Inactivationmentioning
confidence: 99%
“…All non-hemolytic candidate strains retrieved by the modified GABRI method (Fasanella et al, 2013a) from Bangladesh samples were identified as B. anthracis by diagnostic real time PCR on three markers dhp61 (chromosomal), pagA (pXO1) and capC (pXO2), harboring both virulence plasmids (pXO1 and pXO2) (data not shown). The geographic attribution of these isolates within Bangladesh is presented in Table 1.…”
Section: B Anthracis Isolation From Environmental Samples and Initiamentioning
confidence: 99%